Phylogenetic analysis of multidrug resistant E. coli isolates from the urinary tract in Bushenyi district, Uganda using the new Clermont phylotyping method - Odoki, Martin; Aliero, Adamu A.; Tibyangye, Julius; Onkoba, Sarah K.; Bashir, Alkali; Maniga, Josephat N.; Eilu, Emmanuel; Wampande, Eddie; Kato, Charles D.; Agwu, Ezera; Bazira, Joel (African Journal of Microbiology Research, 2020)
Due to the increasing rates of multidrug resistance (MDR) among the Enterobacteriaceae that cause urinary tract infections (UTIs), selection of antimicrobial agents for empirical therapy is becoming a major challenge. This study determined the antimicrobial resistance profiles, multidrug resistance profiles, multiple antibiotic resistance indices (MARI), factors associated with MDR UTIs and the phylogenetic groups of MDR Escherichia coli strains isolated from the urinary tract among patients attending hospitals in Bushenyi District, Uganda. In this cross-sectional study, a total of 86 bacterial uropathogens isolated from 267 study participants suspected to have UTIs were subjected to antimicrobial susceptibility tests using the Kirby Bauer Disk diffusion method. Data for the factors associated with MDR were obtained by the use of questionnaires. Phylogenetic groups of the MDR E. coli were determined using the new Clermont method for phylotyping E. coli. Descriptive and multiple logistic regression statistical tools were used to determine phylogenetic groups, and assess for statistically significant relationship between MDR UTIs and factors suspected to be associated with MDR UTIs respectively. The isolates assigned as group B2 9/12 (75.0%), B1 2/5 (40.0%) and A 2/7 (28.6%) by using the old Clermont method could not be phylotyped using the new Clermont method and were grouped as non-typeable strains of E. coli. Our study demonstrated high prevalence of the non-typeable strains of MDR E. coli, we therefore recommend the use of modern DNA sequencing-based approaches which is the gold standard for genotyping bacteria, that this current study could not afford
Keywords: Phylogenetic analysis; bacterial urinary tract infections; factors associated with